PENGARUH MEDIA FLIP-FOLD LAUNDRY TERHADAP PENINGKATKAN KETERAMPILAN BINA DIRI SISWA AUTIS KELAS 2 SDLB - Eka Wahyu Wulansari; Amelia Rizky Idhartono; Muhammad Nurrohman Jauhari (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Training self-care skills in children with autism is essential to help them achieve greater independence and reduce their reliance on others in daily activities. At Mutiara Hati School in Sidoarjo, several children with autism still experience difficulties in folding clothes as part of their personal care skills. Through the implementation of flip-fold media, the researcher aimed to support and enhance their ability to develop this skill more effectively. This study was designed to examine the extent to which the flip-fold media influences the improvement of clothing-folding skills among children with autism at Mutiara Hati Sidoarjo. The research employed a quantitative approach using a pre-experimental design, specifically the one-group pretest-posttest model. Data collection techniques included performance tests, direct observation, and supporting documentation. Data analysis was conducted using the non-parametric Wilcoxon signed-rank test. The results of the analysis indicated that the calculated Zvalue (Zcount = 2,74) was higher than the critical Zvalue (Ztable = 1,83) at a 10% significance level with a two-tailed test. Therefore, it can be concluded that the use of flip-fold media has a statistically significant effect on improving clothing-folding skills in children with autism at Mutiara Hati Sidoarjo.